Respuestas
Respuesta dada por:
0
P=(x+y)2
P=2x+2y
Q=(x-y)2
Q=2x-2y
![\frac{P+Q}{P-Q} = \frac{(2x+2y)+(2x-2y)}{(2x+2y)-(2x-2y)}
\frac{P+Q}{P-Q} = \frac{(2x+2y)+(2x-2y)}{(2x+2y)-(2x-2y)}](https://tex.z-dn.net/?f=+%5Cfrac%7BP%2BQ%7D%7BP-Q%7D+%3D+%5Cfrac%7B%282x%2B2y%29%2B%282x-2y%29%7D%7B%282x%2B2y%29-%282x-2y%29%7D+%0A)
![\frac{(2x+2y)+(2x-2y)}{(2x+2y)-(2x-2y)} = \frac{2x+2y+2x-2y}{2x+2y-2x+2y}
\frac{(2x+2y)+(2x-2y)}{(2x+2y)-(2x-2y)} = \frac{2x+2y+2x-2y}{2x+2y-2x+2y}](https://tex.z-dn.net/?f=%5Cfrac%7B%282x%2B2y%29%2B%282x-2y%29%7D%7B%282x%2B2y%29-%282x-2y%29%7D+%3D+%5Cfrac%7B2x%2B2y%2B2x-2y%7D%7B2x%2B2y-2x%2B2y%7D+%0A%0A)
![\frac{2x+2y+2x-2y}{2x+2y-2x+2y} = \frac{4x}{4y} = \frac{x}{y}
\frac{2x+2y+2x-2y}{2x+2y-2x+2y} = \frac{4x}{4y} = \frac{x}{y}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%2B2y%2B2x-2y%7D%7B2x%2B2y-2x%2B2y%7D+%3D+%5Cfrac%7B4x%7D%7B4y%7D+%3D+%5Cfrac%7Bx%7D%7By%7D+%0A)
P=2x+2y
Q=(x-y)2
Q=2x-2y
julioso:
el dos hace referencia a que el binomio esta elevado al cuadrado
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años